(o) A certain sequence has a constant second difference of 8. The sixth term of the sequence is 172 and the tenth term is 452. Determine the general term.
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To find the general term of the sequence with a constant second difference of 8, we begin with the understanding that this implies the sequence is quadratic in nature, i.e., of the form \( a_n = An^2 + Bn + C \). Given: - \( a_6 = 172 \) - \( a_{10} = 452 \) We can derive two equations based on these given terms. 1. For \( n = 6 \): \[ 36A + 6B + C = 172 \quad \text{(Equation 1)} \] 2. For \( n = 10 \): \[ 100A + 10B + C = 452 \quad \text{(Equation 2)} \] Next, we need another equation. Since the second difference is constant, we can express this condition in terms of the coefficients: The second difference is \( 2A \). Given that the second difference is 8, we have: \[ 2A = 8 \implies A = 4 \] With \( A = 4 \), we can substitute \( A \) back into our equations. Substituting \( A = 4 \) into Equation 1 and Equation 2, we get: **From Equation 1:** \[ 36(4) + 6B + C = 172 \implies 144 + 6B + C = 172 \implies 6B + C = 28 \quad \text{(Equation 3)} \] **From Equation 2:** \[ 100(4) + 10B + C = 452 \implies 400 + 10B + C = 452 \implies 10B + C = 52 \quad \text{(Equation 4)} \] Now we have two equations (Equation 3 and Equation 4): 1. \( 6B + C = 28 \) 2. \( 10B + C = 52 \) To eliminate \( C \), we can subtract Equation 3 from Equation 4: \[ (10B + C) - (6B + C) = 52 - 28 \implies 4B = 24 \implies B = 6 \] Now substituting \( B = 6 \) back into Equation 3: \[ 6(6) + C = 28 \implies 36 + C = 28 \implies C = 28 - 36 \implies C = -8 \] Now we have all coefficients: - \( A = 4 \) - \( B = 6 \) - \( C = -8 \) The general term of the sequence is: \[ a_n = 4n^2 + 6n - 8 \] Thus, the general term of the sequence is: \[ \boxed{4n^2 + 6n - 8} \]